Polymeric black tea polyphenols (PBPs) inhibit benzo(a)pyrene and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐ butanone‐induced lung carcinogenesis potentially through down‐regulation of p38 and Akt phosphorylation in A/J mice. Issue 2 (27th July 2016) - Hudlikar, Rasika R.; Venkadakrishnan, Varadha Balaji; Kumar, Rajiv; Thorat, Rahul A.; Kannan, Sadhana; Ingle, Arvind D.; Desai, Saral; Maru, Girish B.; Mahimkar, Manoj B.
Abstract : The aim of our study was to evaluate chemopreventive efficacy and possible mechanism of most abundant polyphenolic fraction in black tea, polymeric black tea polyphenols (PBPs), in experimental lung carcinogenesis model. Effect of 1.5% black tea derived PBPs on benzo(a)pyrene [B(a)P] and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK) induced lung lesions were studied over 28 wks. Chemopreventive efficacy was studied using decrease in tumor incidence and/or multiplicity and/or delay in the latency period in A/J mice. Histopathological analysis of lung was carried out post‐carcinogen treatment weeks to analyze the microscopic lung lesions. Inflammation, cell proliferation, and apoptosis markers along with signaling kinases like p38, Akt, and their phosphorylated forms were studied using immunoblotting and immunohistochemistry at 4th, 10th, and 18th wk post‐carcinogen treatment. Administration of PBPs throughout the treatment period significantly decreased the multiplicity of surface tumors as well as microscopic lung lesions, including adenomas. Although tumor incidence and latency period remains unaffected, histopathological evaluation of lung at 6, 10, and 18 wks post‐ carcinogen treatment period showed decrease in tumor multiplicity which was also correlated with different molecular markers. Anti‐ inflammatory action of PBPs was demonstrated by reduced Cox‐2 expression. PBPs down‐regulated the B(a)P and NNK‐induced cell proliferation (diminished PCNA expression, proliferation index, and Bcl‐2 expression) and enhanced apoptosis (increased Bax expression and apoptotic index) potentially through phosphorylation of p38 and Akt. PBPs, most abundant polyphenolic component in the black tea, have chemopreventive effect through inhibition of inflammation, cellular proliferation, and induction of apoptosis possibly via modulation of signaling kinases. © 2016 Wiley Periodicals, Inc.